Short Dance Movie "Renung" as a Media for SelfIntrospection in Increasing Moral Values - siti Risnaini Nurkosasih; Saian Badaruddin; Winda Meirilani (Journal of Dance and Dance Education Studies, 2023)
In the era of the current generation, deviant behavior is developing among young people in almost all corners of the world. This can happen due to environmental factors freedom in accessing social networks and errors in accessing information and the use of information technology. This article aims to explain the process and stages of making short dance films and reveal strategies for overcoming the problem of social deviation through short dance films as a medium for introspection that has a message of moral values. The method used in this article is a qualitative method with descriptive analysis which describes the results of observation and analysis of data phenomena obtained in the field. After analyzing the data, the research results were repeated using triangulation, so that the ideas and concepts of thought could be expressed in a Short Contemporary Dance Film entitled "Renung". The results of this article explain the stages of making a short dance film by containing a storyline, storyboard, and editing techniques so that you can dissect every value in the short dance film. This contemporary dance work "Renung" can be used as a medium for self-introspection to improve moral values in the current and future generations.